Mephedrone and chemsex: a case report. (February 2020) - Anzillotti, L.; Calò, L.; Banchini, A.; Schirripa, M.L.; Marezza, F.; Cecchi, R.
Highlights: A mephedrone-related acute toxicity case. Chemsex: misuse of mephedrone in a sexual context. Effects of mephedrone similar to those of cocaine, amphetamines, and metamphetamines. Mephedrone cross-reacts with methamphetamine screening tests. Abstract: The chemsex or slamsex phenomenon has attracted attention worldwide, with concerns also expressed by health professionals for the spread of sexually transmitted diseases. Mephedrone or 4-methylmethcathinone, a substituted cathinone homolog of ephedrine, is one of the most popular substances used as a cheaper alternative to other traditional drugs. Fatal cases of chemsex are still rare. We present here the first case-report to the best of our knowledge of a mephedrone-related acute toxicity case in Parma (Italy) detected and quantitated in biological specimens (2.0 mg/L in urine sample, 1.1 mg/L in bile and 1.0 mg/L in central blood while 0.8 mg/L in peripheral blood). None of the other most common drugs of abuse could be detected. Autopsy findings such as facies edematosa, oedema and polyvisceral congestion, interstitial petechiae are compatible elements with a death from acute cardio-respiratory failure, with peri-mortem agony of few minutes in which the cardiac hypertrophy, the moderate aortocoronary sclerosis and mephedrone injection have played a substantial role in the evaluation of the final cause due to an accidental acute intoxication with mephedrone.